TEACHING ASSISTANCE FOR PHYSICS EDUCATION STUDENTS IN PHYSICS LEARNING - Nasar, Adrianus; Pau, Mariana Evilina; Boleng, Agustina (LPPM Universitas Flores, 2026)
Physics learning in senior high schools still faces various challenges, including low student participation, the perception that physics is a difficult subject, and limited variation in teaching methods and learning media. One effort to address these challenges is through teaching assistance activities involving physics education students. This activity aims to support physics teachers in the learning process while providing authentic teaching experience for pre-service physics teachers. The teaching assistance was implemented through three stages: preparation, implementation, and evaluation, carried out collaboratively by students and physics teachers at SMAN 1 Ende over one month. The results indicate that the presence of teaching assistant students increases student participation, fosters more enthusiastic learning attitudes, and supports students’ conceptual understanding through direct assistance and group discussions. In addition, this activity provides valuable professional experience for physics education students in classroom management and reflective teaching practices with mentor teachers. Therefore, teaching assistance activities can be considered an effective strategy to enhance the quality of physics learning in senior high schools.